An exponential function is a function of
the form

where a is a positive real number (a > 0)
and
. The domain of f is the set of all
real numbers.
 

 

6 (1, 6)

4

(1, 3)
2

(-1, 1/3) (-1, 1/6)

 

3

2

1

(0, 1)
 

0

1

2

3

Summary of the characteristics of the graph of

a >1 
• The domain is all real numbers. Range is set of 
positive numbers.
• No x­intercepts; y­intercept is 1.
• The x­axis (y=0) is a horizontal asymptote as
With a>1, is an increasing function and 
• 
is one­to­one.
• The graph contains the points (0,1); (1,a), and (­1, 
1/a).
•The graph is smooth continuous with no corners or 
 
 
gaps.

6

(-1, 6)
4

(-1, 3)
2

(0, 1)
 

3

2

1

(1, 1/3) (1, 1/6)
 

0

1

2

3

Summary of the characteristics of the graph of

0 <a <1 
• The domain is all real numbers. Range is set of positive 
numbers.
• No x­intercepts; y­intercept is 1.
• The x­axis (y=0) is a horizontal asymptote as
With 0<a<1, is a decreasing function 
and is one­to­one.
• The graph contains the points (0,1); (1,a), and           
(­1, 1/a).

• 

•The graph is smooth continuous with no corners or 
 
 
gaps.

 

 

10

5

(1, 3)
(0, 1)
0

y=3
 

 

x

10

5

(-1, 3)
(0, 1)
0

−x

y=3
 

 

10

(-1, 5)
y=2

5

(0, 3)
0

−x

y=3

+2

Domain: All real numbers
Range: { y | y >2 } or
Horizontal Asymptote:  y = 2
 

 

More Exponential Functions (Shifts) : 
An equation in the form  f(x) = ax. 
Recall that if   0 < a < 1 , the graph represents 
  exponential decay
and that if  a > 1, the graph represents 
 exponential growth
    Examples:    f(x) = (1/2)x
     f(x) = 2x

Exponential Decay Exponential Growth
We  will take a look at how these graphs
“shift” according to
 
changes in their equation...

Take a look at how the following graphs compare to the original 
graph of  f(x) = (1/2)x  :

   f(x) = (1/2)x          f(x) = (1/2)x + 1      f(x) = (1/2)x – 3

Vertical Shift: The graphs of f(x) = ax + k are shifted
vertically by k units.

 

 

Take a look at how the following graphs compare to the original 
graph of  f(x) = (2)x  :

   f(x) = (2)x            f(x) = (2)x – 3                 f(x) = (2)x + 2  – 3
(3,1)

(0,1)

Notice that f(0) = 1

(-2,-2)

Notice that this graph
is shifted 3 units to the
right.

Notice that this graph
is shifted 2 units to the
left and 3 units down.

Horizontal Shift: The graphs of f(x) = ax – h are shifted
horizontally by h units.
 

 

Take a look at how the following graphs compare to the original 
graph of  f(x) = (2)x  :

   f(x) = (2)x                 f(x) = –(2)x              f(x) = –(2)x + 2  – 3
(0,1)
(0,-1)
(-2,-4)
Notice that f(0) = 1

 

This graph
is a reflection of
f(x) = (2)x . The graph is
reflected over the x-axis.

 

Shift the graph of
f(x) = (2)x  ,2 units to
the left. Reflect the
graph over the x-axis.
Then, shift the graph 3
units down

 

 

A logarithmic function is the inverse of an exponential function.
For the function y = 2x, the inverse is x = 2y.
In order to solve this inverse equation for y, 
we write it in logarithmic form.
x = 2y  is written as y = log2x and is read as “y = the logarithm of x to base 2”.

x
y = 2x

y = log2x
(x = 2y)
 

-3 -2 -1

0

1

2

3

4

y

1
8

1
4

1
2

1

2

4

8

16

x

1
8

1
4

1
2

1

2

4

8

16

-3 -2 -1 

0

1

2

3

4

y

Graphing the Logarithmic Function
y = x

y = 2x

y = log2x

 

 

Comparing Exponential and Logarithmic Function Graphs
y = 2x

y = log2x

The y­intercept is 1.
There is no x­intercept.
The domain is  All Reals 

There is no y­intercept.
The x­intercept is 1.
The domain is  x > 0

The range is  y > 0.

The range is  All Reals 

There is a horizontal asymptote
at y = 0.

There is a vertical asymptote
at x = 0.

The graph of y = 2x has been reflected in the line of y = x, 
to give the graph of y = log2x.
 

 

Logarithms
Consider 72 = 49.
2 is the exponent of the power, to which 7 is raised, to equal 49.
The logarithm of 49 to the base 7 is equal to 2 (log749 = 2).
Exponential
  notation

72 = 49

Logarithmic
      form

log749 = 2

In general:          If         bx  = N,
                        then    logbN = x.
State in logarithmic form:
a)  63 = 216

log6216 = 3

  2 = 16
b)  4

log416 = 2

State in exponential form:

 

a)  log5125 = 3

53 = 125

b)  log2128= 7

27 = 128

Logarithms
State in logarithmic form:

1

a) y =  
2

x
1.4

b) 2

x
log 0.5 y =
1.4

= 32

log2 32 = 3x + 2

1.4log0.5 y = x

 

3x+ 2

 

Evaluating Logarithms
1.  log2128

Think – What power must 
you raise 2  to, to get 128?

log2128 = x
         2x = 128
         2x = 27
               x = 7

3.  log556 = 6
4.  log816

log816 = x
       8x = 16
      23x = 24
          3x = 4
 

4
x=
3

2.  log327
log327 = x
       3x = 27
       3x = 33
             x = 3

Note:
log2128 = log227
                    
= 7
  log327 = log333
              = 3

logaam = m   because logarithmic and 
                     exponential functions are
                     inverses.  
5.   log81
log81 = x
loga1 = 0
     8x = 1
     8x = 80
         x = 0
 

Evaluating Logarithms
6.       
log4(log33 )
8

log48 = x
     4x = 8
    22x = 23
    
  2x = 3
3
x=
2

2

log2 8

=2

log2 2 3

8.  

 = 23
 = 8

 

3
log
7.  
4 8
log 4 3 8 = x

x

4 =3 8
2x

3

2 =2 3
2x = 1
1
x=
2
9.  Given log165 = x, and log84 = y,
     express log220 in terms of x and y.
log165 = x
log84 = y
16x = 5
8y = 4
 24x = 5
23y = 4
 log220 = log2(4 x 5)
             = log2(23y x 24x)
3y + 4x
)
              = log2(2
             = 3y + 4x

Logarithmic Functions
x = 2y    is an exponential equation.
Its inverse (solving for y) is called a 
  logarithmic equation.
Let’s look at the parts of each type of equation:
Logarithmic Equation
Exponential Equation
y = loga x
x = ay
exponent /logarithm
base
number
 

It is helpful to remember: “The logarithm of a number is the 
power to which the base must be raised to get the given 
 
number.”

Example:  Rewrite in exponential form and 
solve      loga64 = 2       
base number exponent
2

                    a  = 64
  a =  8
Example:  Solve log5 x = 3
Rewrite in exponential form:
3

    5  = x
    x = 125
 

 

1
=y
Example:  Solve   log 7
49

          

y

7   =   1 
          49
                    y = –2

An equation in the form  y = logb x where b > 0 
and b ≠ 1 is called a logarithmic function.
Logarithmic and exponential functions are inverses of 
each other
x

logb b  = x

     
 

log  x  
b

b

= x

 

Examples.  Evaluate each:
4
a.    log8 8  

  

x

logb b  = x

   log8 8  =  4
4

[log  (3y – 1)]
6

b.   6
        

log  x  
b

b

 

= x 

  =  3y – 1

[log  (3y – 1)]
6

6

Here are  some special logarithm values:
0
1.   loga 1 = 0     because  a  = 1 
2.   loga a = 1     because  a1 = a 
 

3.   loga a  = x     because  a  = a  
x

  x

x

 

 

Laws of Logarithms

Consider the following two problems:
Simplify

   log3 (9 • 27)
2

3

= log3 (3 • 3 ) 
2 + 3

= log3 (3

)

          =          2 + 3 
Simplify

 

   log3 9 + log3 27
2

= log3 3  + log3 3

=     2     +     3
These examples suggest the Law:
Product Law of Logarithms:
 
 
For all positive numbers m, n and b where b ≠ 1, 

Consider the following:
 81
a. log3  
27

 
  =   log3 34     
         

3

=   log3 34 – 3 

         b. log3 81 − log3 27
= log3 34  –  log3 33
=         4  –    3

=          4 – 3
These examples suggest the following Law:
Quotient Law of Logarithms:
For all positive numbers m, n and b where b ≠ 1, 
logb  m  =  logb m – logb n
        
    n 
 

    

The Product and Quotient Laws
Product Law:

logb(mn) = logbm + logbn

The logarithm of a product equals 
the sum of the logarithms.
 Quotient Law:

 m
log b   = log b m − log b n
n

The logarithm of a quotient equals
 the difference of the logarithms. 

Express

AB
log 3 
C  as a sum and difference of logarithms:
AB

log 3 
C  = log3A + log3B ­ log3C

Evaluate:      log210 + log212.8

 

= log2(10 x 12.8)
= log2(128)
= log2(27)

 

Simplifying Logarithms
Solve:  x = log550 ­ log510
 50
= log 5  
10

 x = log55
    = 1

Given that log79 = 1.129, find the value of log763:
log763 = log7(9 x 7)
           = log79 + log77
           = 1.129 + 1
           = 2.129
Evaluate:  x = log45a + log48a3 ­ log410a4
 5a × 8a3 
x = log4 

4
 10a 

x = 1

 40a4 
x = log4 
4
 10a 
 

x = log44

 

3

    = log3 (32)4
    = log3 32 • 4
         

    =         2 • 4
 
b.  4 log3 9

 

    = (log3 32) • 4
    =      2       • 4
These examples suggest the following Law:
Power Law of Logarithms:
For all positive numbers m, n and b where b ≠ 1, 
 
 
p
logb  m   = p •  logb m

The Power Law
Power Law:

logbmn  = n logbm
n
d

n
log b m = log b m
d

The logarithm of a number to a power equals the 
power times the logarithm of the number.
1
Express as a single log: 3 log5 3 + 2 log5 2 + log5 4
2
1
= log 5 33 + log 5 22 + log 5 4 2
1
 3

2
2
= log 5  3 × 2 × 4 


= log 5 (27 × 4 × 2)
 

= log5216
 

Applying the Power Laws
Evaluate: log 5 25 125 + log3 813 243
1
2

= log 5 52 + log 5 125 + log 3 34 + log3 243
1
1
3
5
= 2 log 5 5 + log 5 5 + 4log3 3 + log 3 3
2
3

1
1
= 2(1) + (3) + 4(1) + (5)
2
3

1
3

55
=
6

4
Given that log62 = 0.387 and log65 = 0.898 solve  log 6 20 :

log 6

4

1
20 = log6 (2 × 2 × 5)
4
1
= [log 6 2 + log6 2 + log 6 5]
4
=

 

1
(0.387 + 0.387 + 0.898)
4

= 0.418

 

Applying the Power Laws

(

Evaluate: 3

log5 2

)(3

log 5 4

)

(log 5 2 + log 5 4)

=3
log5 (2 × 4)
=3
log5 8
=3

If log28 = x, express each in terms of x: 
b)  log22

a)  log2512
= log283
= 3log28
 
= 3x

 

 log28 = x
log223 = x
3log22 = x
x
log 2 2 =
3

More examples:  Given log12 9  = 0.884 and
        
log12 18 = 1.163, find each:
a.  
 3
log12           = log12    9  
 4
      12
  = log12 9 – log12 12 
                                 

b.  log12 2

 

=  0.884  –     1         

  =     –0.116
 = log12   18  
               9 
=  log12 18 – log12 9 
= 1.163 – 0.884  
 
=   0.279

Example:  Solve       2 log6 4 –  1 log6 8 =  log6 x
   

log6 42 – log6 81/3 =  log6 x
log6 16 – log6 2   =  log6 x
 log6 (16/2)          =  log6 x
   16/2        =    x
               x = 8

 

 

Natural Exponential Functions 
The most commonly used base for exponential and 
logarithmic functions is the irrational number e.
1 m
e = lim (1 + ) ≈ 2.71828
m →∞
m

• Exponential functions to base e are called natural 
exponential functions and are written y = ex. 
• Natural exponential function follows the same rules 
as other exponential functions.
 

 

Exponential Function
y > 0 for all x

10
9

passes through (0,1)

8

positive slope increasing

y = ex

7
6
5
4
3
2
1
0
-3

 

-2

-1

0

1

2

3

 

4

Natural Logarithms 

• logarithms to base e (≈ 2.71828)
• loge x  or  ln x (Note: These mean the same thing!)
• ln  x    is  simply  the  exponent  or  power  to  which  e
must be raised to get x.
y = ln x  ⇔  x = ey
• Since natural exponential functions and natural logarithmic 
functions  are  inverses  of  each  other,  one  is  generally 
helpful in solving the other.  Mindful that ln x signifies the 
power to which e must be raised to get x, for a > 0,

eln x = x [Let’s y = ln x  and x = ey ⇒ x = elnx] 
    ln ex = x [Let’s y = ln ex ⇒ ey  = ex ⇒ y = x] 
eln x = ln ex = x
 

 

Ex)  the natural logarithm of x





 

ln e = 
ln 1 = 
ln 2 =
ln 40 = 
ln 0.1 =

 

Ex)  the natural logarithm of x
1
• ln e = 1
    since e  = e
0
• ln 1 = 0
    since e  = 1
• ln 2 = 0.6931...    since e0.6931...  = 2
• ln 40 = 3.688...    since e3.688.. = 40
­2.3025.

• ln 0.1 = ­2.3025   since e

 

 

 = ­1

Natural Logarithmic Function
y > 0 for x > 1
y < 0 for 0 < x < 1
passes through (1,0)
positive slope
(increasing)

5
4

y = ln x

3
2
1
0
-1

0

1

2

3

4

5

6

7

8

9

-2
-3
-4
-5

 

 

10

Sign up to vote on this title
UsefulNot useful